Characterisation of the germ cell tumours seen at the Red Cross War Memorial Children's Hospital (1956-1995) - Gordon, Alan Ian (Division of Anatomical Pathology, 2017)
The aim of the current study is the characterisation (primarily pathological, but with clinical correlation) of the germ cell tumours seen in the Pathology Department of the Red Cross Childrens Hospital since its inception in 1956 (through to the year 1995, date of commencement of the study). Study population: Infants and children from birth to 13 years of age (of all population groups, but predominantly those from the disadvantaged black and mixed race communities of the Greater Cape Town metropolitan area).